Методологічні проблеми публічного екологічного управління в умовах соціально-політичних трансформацій. (Zaporizhzhia Historical Review, 2021)
The main conceptual approaches, which are used in modern environmental researches, which includes the public administration as main contains, is analyzing at the article. The problematical field at the methodology of environmental researches at the context of public administration discourse is investigating by the author.